Six feet above: the look - Choy, Cliff Wai Chuang (2018)
The cinematography of Six Feet Above is an exploration of finding a balance while combining various visual styles into a short film. The visual idea of the film evolves as the script and characters shape themselves. The visual style revolves around the characters and the narrative, which is mainly divided into three different segments in terms of visual space and emotional space. We follow the protagonist, Sarah, as she travels to-and-fro the spaces and uncovers new information and obstacles.